Training of Lithuanian modern pentathlonists in the fourth year of the Olympic cycle - Milasius, K.; Moskvieiovas, J.; Skernevicius, J.; Raslanas, A.; Karosiene, J. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
Lithuanian modern pentathlonists were greatly successful in 2004. They won the gold medals in the world and European championships and a silver medal in the Olympic games in Athens. The aim of the current work was to analyze the structure of training in the last year of the Olympic cycle, the achieved results and to assess the dynamics of athletes`s physical and functional abilities over the period.